2005
DOI: 10.1007/s00213-005-0221-2
|View full text |Cite
|
Sign up to set email alerts
|

Desipramine attenuates working memory impairments induced by partial loss of catecholamines in the rat medial prefrontal cortex

Abstract: These data suggest that moderate loss of DA and NE in the prefrontal cortex is sufficient to impair cognitive function, and these behavioral effects are attenuated by inhibition of the NE transporter.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 58 publications
(78 reference statements)
0
27
0
Order By: Relevance
“…For example, 5-HT depletion in this region reduces exploratory behavior (Lipska, et al, 1992) and lowers consumption of sucrose-ethanol solutions in rats (Deckel, et al, 1997), both behaviors consistent with these models of depression. Dopaminergic depletion in this region has been found to impair cognitive performance (Clinton, et al, 2006), and similarly, depletion of 5-HT in the mPFC also results in perseverative responding to a stimulus, suggesting a type of cognitive inflexibility similar to behavior seen in humans with obsessive-compulsive disorder . These effects are important to consider in the present rat model because people suffering from eating disorders, some of which involve HCR and intermittent access to PF, present symptoms of impaired concentration and depression and are more likely than the healthy, non-disordered population to suffer from obsessive-compulsive disorder and a rigid style of thinking (Kaye, et al, 2004;Speranza, et al, 2001).…”
Section: Discussionmentioning
confidence: 93%
“…For example, 5-HT depletion in this region reduces exploratory behavior (Lipska, et al, 1992) and lowers consumption of sucrose-ethanol solutions in rats (Deckel, et al, 1997), both behaviors consistent with these models of depression. Dopaminergic depletion in this region has been found to impair cognitive performance (Clinton, et al, 2006), and similarly, depletion of 5-HT in the mPFC also results in perseverative responding to a stimulus, suggesting a type of cognitive inflexibility similar to behavior seen in humans with obsessive-compulsive disorder . These effects are important to consider in the present rat model because people suffering from eating disorders, some of which involve HCR and intermittent access to PF, present symptoms of impaired concentration and depression and are more likely than the healthy, non-disordered population to suffer from obsessive-compulsive disorder and a rigid style of thinking (Kaye, et al, 2004;Speranza, et al, 2001).…”
Section: Discussionmentioning
confidence: 93%
“…This was to validate the mPFC-dependency of working memory (Larsen and Divac, 1978;Murphy et al, 1996;Zahrt et al, 1997;Baeg et al, 2003;Birnhaum et al, 2004;Clinton et al, 2005). Under ketamine HCl (30 mg/kg) and xylazine (2.5 mg/kg) anesthesia, rats were mounted in a stereotaxic instrument with non-puncture ear bars (Stoelting, Wood Dale, IL), and bilateral mPFC lesions were made by passing constant current (1 mA, 10 s; Ugo Basile, Comerio, Italy) through a stainless steel insect pin (#00) that was insulated with epoxy, except for ∼0.5 mm at the tip (coordinates: from bregma, +3.7 and +2.7 mm anterior, ±0.5 mm lateral, and −3.2, 4.2, and 5.2 mm ventral from the skull).…”
Section: Pfc Lesionsmentioning
confidence: 99%
“…The delayed alternation task (DAT), employing a T-maze or a Figure-8 maze, is widely used in lesion, pharmacological and unit recording experiments that investigate working memory processes in rodents (Olton et al, 1979;Morris et al, 1986;Murphy et al, 1996;Zahrt et al, 1997;Baeg et al, 2003;Schoenbaum et al, 2003;Birnhaum et al, 2004;Clinton et al, 2005; see also Uylings et al, 2003;Dalley et al, 2004). In a typical DAT, the animal is cued (via discrete, contextual or spatial stimulus) to make a particular choice response to obtain a reward, but is prevented from responding until after some delay period.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, damage to the PFC produces impairments in various working memory tasks in humans and non-human primates (Kolb 1990;Fuster 1997;Stuss and Alexander 2000). Additionally, recording and brain imaging studies found neural activity correlates of working memory, i.e., increased PFC activity during the delay period (Fuster and Alexander 1971;Kubota and Niki 1971;Funahashi et al 1989).In rodents, a delayed alternation task (DAT; employing T, radial-arm, and figure-eight mazes) has been widely used to further investigate the PFC-working memory hypothesis (Murphy et al 1996;Zahrt et al 1997;Baeg et al 2003Baeg et al , 2007Schoenbaum et al 2003;Birnbaum et al 2004;Clinton et al 2006). In this task, the animal is typically cued (via a discrete or spatial stimulus) to make a choice response to obtain a reward, but is prevented from responding until after some delay period (or working memory demand) has been imposed.…”
mentioning
confidence: 99%
“…In rodents, a delayed alternation task (DAT; employing T, radial-arm, and figure-eight mazes) has been widely used to further investigate the PFC-working memory hypothesis (Murphy et al 1996;Zahrt et al 1997;Baeg et al 2003Baeg et al , 2007Schoenbaum et al 2003;Birnbaum et al 2004;Clinton et al 2006). In this task, the animal is typically cued (via a discrete or spatial stimulus) to make a choice response to obtain a reward, but is prevented from responding until after some delay period (or working memory demand) has been imposed.…”
mentioning
confidence: 99%